Germ Cell Derivation from Pluripotent Stem Cells for Understanding In Vitro Gametogenesis - Tae-Kyung Hong; Jae-Hoon Song; So-Been Lee; Jeong-Tae Do (Cells, 2021)
Assisted reproductive technologies (ARTs) have developed considerably in recent years; however, they cannot rectify germ cell aplasia, such as non-obstructive azoospermia (NOA) and oocyte maturation failure syndrome. In vitro gametogenesis is a promising technology to overcome infertility, particularly germ cell aplasia. Early germ cells, such as primordial germ cells, can be relatively easily derived from pluripotent stem cells (PSCs); however, further progression to post-meiotic germ cells usually requires a gonadal niche and signals from gonadal somatic cells. Here, we review the recent advances in in vitro male and female germ cell derivation from PSCs and discuss how this technique is used to understand the biological mechanism of gamete development and gain insight into its application in infertility.